Dawni Mistrzowie Francuscy - JAMRY, F. ([s.n.])
Gawot - Jan Baptistyste Lully. Gawot i Musette - Jan Baptistyste Lully. Aria - Fransiszek Couperin. Wiatraczki - Franciuszek Couperin. Rigaudon - Jan Filip Rameau. Gawot - Jan Filip Rameau. Sarabanda i Allegro - Jan Maria Leclair. Allegro - Jan Maria Leclair. Aria - Franciszek Francoeur. Tambourin - Jan Jozef Mondonville